Influence of Pasteurella haemolytica A1 crude leukotoxin on bovine neutrophil chemiluminescence. - Czuprynski, C J (1990)
Pasteurella haemolytica A1 crude leukotoxin (25%, vol/vol) rapidly diminished the bovine neutrophil chemiluminescence response to opsonized zymosan. This inhibition was neither prevented nor reversed by 75 mM sucrose. Dilute leukotoxin did not directly stimulate neutrophil chemiluminescence nor did it alter the chemiluminescence response of the neutrophils to opsonized zymosan.